Socio-economic factors associated with mental health outcomes during the COVID-19 pandemic in South Korea - Lee, Seo Yoon; Lee, Jung Jae; Lee, Hooyeon (Frontiers in Public Health, 2022)
Background: Individuals are at an increased risk of adverse mental health outcomes during the COVID-19 pandemic. To reduce the impact on mental health outcomes that was induced by national level polices which may influence individual to community level, exploring the comprehensive relations between individual and environmental factors are needed. To examine socio-ecological factors associated with mental health outcomes including depressive and anxiety symptoms with the perspective of support to provide interventions that help the community during future disease outbreaks. Method: From November 5 to November 20, 2020, a cross-sectional and population-based study was conducted to assess the socio-ecological factors of mental health outcomes during the COVID-19 pandemic. One thousand participants, aged 20-69 years, in Chungnam Region, South Korea, were included in this study. Multiple linear regression models were used to examine the association between socio-ecological factors and mental health outcomes. The primary outcomes were individuals’ mental health outcomes which are measured by PHQ-9 and GAD-7 scores. Results: Of the 1,000 participants, the average of PHQ-9 was 4.39 and GAD-7 was 3.21 during the COVID-19 pandemic. Specifically, the participants with moderate or severe levels of PHQ-9 and GAD-7 were 12.6% and 6.8%, respectively. Higher levels of depressive and anxiety symptoms were associated with participants who were single, reported a lower household income, had decreased support from friends or family, and increased stress from the workplace or home. In subgroup analyses by age, gender, and household income, a similar trend was reported in individual and interpersonal level factors. There were significant associations between regional level factors including Gross Regional Domestic Product, mental health institution, psychiatrist, and nurse-to-population ratios, and individuals’ mental health outcomes. Conclusions: The management of depressive and anxiety symptoms of individuals during the infectious disease pandemic was better explained by individual and interpersonal characteristics rather than regional level factors, highlighting the need for more policies aimed at these lower levels.